Option B:
is the correct answer
Step-by-step explanation:
Given functions are:
![f(x) = 3x^2-5x+13\\g(x) = 2x-7](https://tex.z-dn.net/?f=f%28x%29%20%3D%203x%5E2-5x%2B13%5C%5Cg%28x%29%20%3D%202x-7)
We have to find g(f(x))
So,
![g(f(x)) = 2(f(x))-7\\= 2(3x^2-5x+13)-7\\=6x^2-10x+26-7\\= 6x^2-10x+19](https://tex.z-dn.net/?f=g%28f%28x%29%29%20%3D%202%28f%28x%29%29-7%5C%5C%3D%202%283x%5E2-5x%2B13%29-7%5C%5C%3D6x%5E2-10x%2B26-7%5C%5C%3D%206x%5E2-10x%2B19)
Hence,
Option B:
is the correct answer
Keywords: Functions, Composition
Learn more about functions at:
#LearnwithBrainly
Answer:
center:-2,3
Radius:10
Step-by-step explanation:Happy to help :)
Answer:
-23
Step-by-step explanation:
We are given the functions;
h(x) = 5x - 3 and j(x) = -2x
Now, we want to find h[j(2)]
j(2) = -2(2)
j(2) = -4
Thus;
h(-4) = 5(-4) - 3
h(-4) = -20 - 3
h(-4) = - 23
I can't help without a question.
We have to draw the model for 42 divide 7 . In order to draw the model we use below steps.
- Draw 7 boxes to represent 7 groups.
- Assume 42 as the number which represents the total of these 7 groups.
- Put a question mark at the first box.
Attached is the model to represents 42 divide 7 .
In the question mark we should put 6. Hence, when we add 6 to 7 times that will be equal to 42.